A new species of Cirrophorus (Annelida: Paraonidae) from Mediterranean organically enriched coastal environments, with taxonomic notes on the family. (10th August 2017) - Langeneck, Joachim; Barbieri, Michele; Maltagliati, Ferruccio; Castelli, Alberto
Abstract : Cirrophorus nikebianchii sp. nov. is described from brackish-water and organically enriched marine environments of the Mediterranean Sea. The new species is characterized by a very small prostomial antenna and a high number of branchiae pairs. A phylogenetic analysis carried out through the use of three molecular markers (16S rRNA, 18S rRNA and COI) supports the distinction between C. nikebianchii and C. furcatus, a closely related species with which it has been misidentified. Preliminary results obtained show that the genera Cirrophoru s and Paradoneis are not reciprocally monophyletic, with uncertain relationships with the remaining genera of Paraonidae. This outcome suggests that the evolutionary history of Paraonidae is less straightforward than previously supposed. Moreover, the uncertainty about the taxonomic status of Paraonides neapolitana, type species of the genus Paraonides, makes the revamping of the taxonomy of Paraonidae more challenging. Awaiting support from studies including more species, and based on morphological and genetic data as well, we suggest to provisionally maintain the current use of Cirrophorus and Paradoneis, and to assign to Paraonella the species traditionally assigned to Paraonides.